(untitled) (Research, Society and Development, 2021)
Primary molars with furcation lesions have a negative impact on the child’s quality of life. We determined the prevalence of furcation lesions and their influence on the root resorption process in primary molars. It is Cross-sectional study of patients aged 3 to 12 years that was apply a health questionnaire was applied and the teeth were submitted to physical examination using the International Caries Detection and Assessment System (ICDAS) and periapical radiography. Criteria for radiographic interpretation were established and assessments performed by three different specialists. The kappa coefficient measured interexaminer agreement and level of significance of 5% was adopted for all tests. The sample consisted of 26 patients and 50 primary molars. The second molar received ICDAS score 6 in 38.5% of the sample. The interexaminer agreement was almost perfect between the radiologist and pediatric dentist for caries depth on the mesial (K=0.97) and occlusal surface (K=0.97); In root resorption for mesial (K=0.89) and distal (K=0.93). The detection of furcation lesions was present in 42.3% of the sample; 50% of the teeth had at least 1/3 of the mesial root resorbed and 75% of the distal root and the presence of furcation lesions in primary molars influenced root resorption.